STRATEGI GURU AGAMA HINDU DALAM MENGINTEGRASIKAN NILAI TRI MURTI UNTUK PENDIDIKAN KARAKTER SISWA SMP N 3 SINGARAJA - Ekawilayanti, Luh; Ni Rai Vivien Pitriani; Putu Subawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In the modern era, the degradation of morals and ethics is a pressing issue that must be addressed within the education system. Consequently, Hindu Religious Education teachers must adopt innovative and collaborative instructional strategies. The research questions addressed are: (1) Why do Hindu Religious Education teachers employ strategies to integrate *Tri Murti* values into character education for students at SMP N 3 Singaraja? (2) How do these teachers carry out the process of integrating *Tri Murti* values for student character education at SMP N 3 Singaraja? (3) What are the implications of integrating *Tri Murti* values for student character education at SMP N 3 Singaraja regarding Hindu Religious Education and the wider community? The theories applied include: (1) Structural-Functional Theory, (2) Constructivism Theory, and (3) Social Learning Theory. This study employs a qualitative descriptive method. Informants were selected using purposive sampling, and data collection involved observation, interviews, documentation, and literature review. Data analysis encompassed data collection, data reduction, data presentation, and conclusion drawing. The research findings indicate that: (1) The integration of *Tri Murti* values at SMP N 3 Singaraja successfully transformed he aspect of divinity into a foundation for student character that is both adaptive and contextual. (2) The integration process proceeds through three adaptive learning phases: the *Brahma* phase to stimulate creativity, the *Wisnu* phase to foster cooperation, and the *Siwa* phase as a space for self-evaluation. (3) The continuity of these divine values builds robust mental resilience and emotional maturity. The data analysis leads to the conclusion that the strategies employed by Hindu Religious Education teachers to integrate *Tri Murti* values into character education can influence student behavior in both academic and social contexts.